The bear - Krivak, Andrew (Bellevue Literary Press, 2020)
"In an Edenic future, a girl and her father live close to the land in the shadow of a lone mountain. They possess a few remnants of civilization: some books, a pane of glass, a set of flint and steel, a comb. The father teaches the girl how to fish and hunt, the secrets of the seasons and the stars. He is preparing her for an adulthood in harmony with nature, for they are the last two left. But when the girl suddenly finds herself alone in an unknown landscape, it is a bear that will lead her back home through a vast wilderness, which offers the greatest lessons of all, if she can only learn to listen. A cautionary tale of human fragility, of love and loss, The Bear is a stunning tribute to the beauty of nature's dominion"--